2006
DOI: 10.1111/j.1600-0579.2006.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Noise levels in dental schools

Abstract: Objective: To measure and analyse noise levels in the learning-teaching activities at the Dental School of the University of Porto (Portugal). Materials and methods: Sound levels were measured in five different practice areas and laboratories, selected as representative of a variety of learning-teaching activities. The noise levels were determined using a precision sound level meter that was positioned at ear level and at 1 m distance from the operator. Results: The noise levels registered vary between 60 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 9 publications
3
17
0
1
Order By: Relevance
“…This study concluded that the average daily use of hand pieces was approximately 14.5 minutes, and noise levels of the devices ranged from 76 to 105 dBA (11). More recent studies have found that despite the changes in technology, including the transition from micromotor hand-pieces to air-turbine hand-pieces, produce similar ranges of noise levels (4,6,12,13,2123,26–31), and these levels are consistent with our results, as well. Several previous studies have noted high variability in dental noise levels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study concluded that the average daily use of hand pieces was approximately 14.5 minutes, and noise levels of the devices ranged from 76 to 105 dBA (11). More recent studies have found that despite the changes in technology, including the transition from micromotor hand-pieces to air-turbine hand-pieces, produce similar ranges of noise levels (4,6,12,13,2123,26–31), and these levels are consistent with our results, as well. Several previous studies have noted high variability in dental noise levels.…”
Section: Discussionsupporting
confidence: 92%
“…Noise levels associated with clinical handpieces ranged from 76–105 A-weighted decibels (dBA) , and suction ranged from 74–80 dBA, in a 1979 US Army study (11), similar to levels of 70–82 dBA for clinical handpieces and 82–90 dBA for cleaners and scalers reported in a separate study (12). Reports in the contemporary literature suggest that noise levels may not have declined substantially over the intervening 30+ years; mean levels of 70–76 dBA for clinical handpieces and suction were reported in 1998 (13), 66–76 dBA in 2006 (14) 64–97 dBA in 2011 (15) and 75–84 dBA in 2014 (15). It is important to note the majority of these measurements were brief measurements made in close proximity to operating dental instruments, rather than measures of personal exposure, and that noise exposures associated with ultrasonic devices are not completely captured with the A-weighting network used for virtually all occupational exposure assessments, as A-weighting heavily deweights ultrasonic exposures (i.e., exposures to noise frequencies>20 kHz).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…También se han observado cambios en la amplitud de las emisiones otoacústicas para las frecuencias 4 y 6 kHz del oído izquierdo y 6 kHz del oído derecho al comparar las mediciones previas y posteriores a una jornada de actividad práctica dental de los estudiantes 13 . En las clases prácticas dentales, el ambiente acústico se caracteriza por altos niveles de ruido en relación con otras carreras, debido a que el sonido producido por el instrumental dental se ve potenciado por el uso de varios equipos al mismo tiempo 14 . Resulta de interés estudiar el estado del sistema auditivo de los jóvenes estudiantes de la carrera de odontología, quienes están inmersos en un ambiente con elevados niveles de ruido en sus actividades prácticas desde muy temprana edad.…”
Section: Introductionunclassified
“…Dentists and dental auxiliaries are exposed to noise of different sound levels while working in dental clinics and laboratories (2,4). Dental laboratory machine, dental hand-piece, ultrasonic scalers, amalgamators, high speed evacuation, and other items produce noise at different sound levels which is appreciable (5). Hearing problems were reported by few dentists in a study (6).…”
Section: Introductionmentioning
confidence: 99%